Biomass and Nitrogen Content of Hairy Vetch–Cereal Rye Cover Crop Mixtures as Influenced by Species Proportions. (1st November 2015) - Poffenbarger, Hanna J.; Mirsky, Steven B.; Weil, Raymond R.; Maul, Jude E.; Kramer, Matthew; Spargo, John T.; Cavigelli, Michel A.
Abstract : The performance of legume–grass cover crop mixtures may be influenced by the species proportions in mixture. The objectives of this study were to: (i) evaluate total aboveground biomass and species biomass proportions resulting from different hairy vetch (legume; Vicia villosa Roth)/cereal rye (grass; Secale cereale L.) sown proportions, (ii) characterize aboveground N content and C/N ratios in response to species biomass proportions, and (iii) quantify biologically fixed nitrogen (BFN) in hairy vetch and the potential transfer of BFN to associated cereal rye. A gradient of six sown proportions ranging from 100% cereal rye to 100% hairy vetch was drilled in fall 2011 and 2012 at two sites in Beltsville, MD, and sampled for biomass, C and N content, and BFN the following spring. Hairy vetch monocultures produced less biomass than cereal rye monocultures, but biomass levels were similar between cereal rye monocultures and mixtures. Cereal rye was usually the dominant species in mixtures. Nitrogen content increased from 64 to 181 kg ha −1 and C/N ratio decreased from 83 to 16 as hairy vetch biomass increased from 0 to 100%. Nitrogen content was estimated to plateau when hairy vetch reached approximately 50% of the total biomass. Averaged across site‐years, BFN made up 63 and 86% of hairy vetch N in monoculture and mixture, respectively. For mixtures, a wide range of sown proportions produced >8 Mg ha −1 biomass, but achieving maximum N content and low C/N ratios required a hairy vetch/cereal rye seeding rate of 27:34 kg ha −1 .